Dihydroartemisinin-piperaquine effectiveness for seasonal malaria chemoprevention in settings with extended seasonal malaria transmission in Tanzania - Richard Mwaiswelo; Billy Ngasala; Frank Chaky; Fabrizio Molteni; Ally Mohamed; Samwel Lazaro; Bushukatale Samwel; Bruno P. Mmbando (Scientific Reports, 2024)
Abstract Effectiveness of dihydroartemisinin-piperaquine (DP) as seasonal malaria chemoprevention (SMC) was assessed in Nanyumbu and Masasi Districts. Between March and June 2021, children aged 3–59 months were enrolled in a cluster randomized study. Children in the intervention clusters received a monthly, 3-days course of DP for three consecutive months regardless of malaria infection status, and those in the control clusters received no intervention. Malaria infection was assessed at before the first-round and at 7 weeks after the third-round of DP in both arms. Malaria prevalence after the third-round of DP administration was the primary outcome. Chi-square tests and logistic regression model were used to compare proportions and adjust for explanatory variables. Before the intervention, malaria prevalence was 13.7% (161/1171) and 18.2% (212/1169) in the intervention and control clusters, respectively, p < 004. Malaria prevalence declined to 5.8% (60/1036) in the intervention clusters after three rounds of DP, and in the control clusters it declined to 9.3% (97/1048), p = 0.003. Unadjusted and adjusted prevalence ratios between the intervention and control arms were 0.42 (95%CI 0.32–0.55, p < 0.001) and 0.77 (95%CI 0.53–1.13, p = 0.189), respectively. SMC using DP was effective for control of malaria in the two Districts. Trial registration: NCT05874869, https://clinicaltrials.gov/ 25/05/2023.